Accumulation and subcellular distribution of heavy metal in Paulownia fortunei cultivated in lead-zinc slag amended with peat. Issue 11 (19th September 2019) - Zhang, Qianni; Chen, Yonghua; Du, Lu; Zhang, Mengying; Han, Liangze
Abstract: The contamination of toxic heavy metals was a major issue of concern in the last century. A fast-growing metal-accumulating woody plant is a promising approach for the remediation of toxic heavy metal. In this study, the transportation of heavy metals (Pb, Zn, Cu, and Cd) in Paulownia fortunei cultivated in lead-zinc slag amended with different mass ratios of peat (CK: 0; T1: 10%; T2: 20%; T3: 30%) was investigated, as well as the subcellular distribution of Pb, Zn, Cu, and Cd in Paulownia fortunei. The results showed that the accumulation content of Pb, Zn, Cu, and Cd in Paulownia fortunei were increased with peat amendment, which was in the range of 4.216 ∼ 6.853, 20.905 ∼ 23.017, 1.898 ∼ 2.572, and 0.530 ∼ 0.616 mg/pot, respectivly. The experimental group with 30% dose of peat showed the best performance on the accumulation content of Pb, Zn, Cu, and Cd, with increase rates (compared to control) of 4.088, 10.573, 1.360, and 0.294 mg/pot, respectively. The bioconcentration, translocation and transfer quantity factor of Pb, Zn, Cu, and Cd were less than 1. Fixation of cell wall and compartmentalization of vacuolar appeared to play an important role in reducing the toxicity of Pb, Zn, Cu, and Cd.